Forest and Land Fires Challenges: Unraveling West Kalimantan's Local Politics in Environmental Governance - Hestiantini, Adila Puspa (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, 2023)
Environmental Policy in West Kalimantan is an important issue because this province is in an area that is prone to environmental problems such as forest degradation. West Kalimantan has significant environmental problems. One of them is forest and land fires which cause air pollution (smog) in the West Kalimantan area which is more pronounced in the Mempawah, North Kayong, Kuburaya, Pontianak and surrounding areas. Then Deforestation and Habitat Destruction, which is forest encroachment and land conversion for the development of agricultural activities (oil palm) which results in habitat destruction for wildlife and also worsens the quality of the surrounding environment. in this way we will find out what the West Kalimantan government's policy is regarding the environmental issue (karhutla) of forest and land fires in 2023.